Hubungan Tingkat Kecerdasan Spiritual dengan Perilaku Kesopanan Siswa Kelas VI - Mirani Putri; Sitti Jauhar; Awaluddin Muin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The problem in this study is the lack of spiritual intelligence that makes students have impolite behavior. This study is a quantitative study with a correlation design that aims to determine the relationship between the level of spiritual intelligence and the politeness behavior of the sixth graders of SD Cluster III. The results showed that there was a significant relationship between spiritual intelligence and politeness behavior of class VI SD Cluster III students with tcount (11.02) greater (>) ttable value (1.65821) which means H0 is rejected and H1 is accepted. Based on the data analysis, the key to spiritual intelligence will have an impact on student behavior. So, increasing the level of spiritual intelligence of students will have good politeness behavior. From these conclusions, the impact resulting from this study is known that high spiritual intelligence will affect the behavior of students' politeness.